Pendidikan Agama Islam Berwawasan Interdisipliner Sebagai Corak dan Solusi Pendidikan Agama Islam Era 4.0 - Rahmat Rahmat (Tribakti: Jurnal Pemikiran Keislaman, 2019)
Islamic Education (PAI) in Higher Education is a subject that has received a lot of criticism from various circles because PAI which is also referred to as a scientific discipline is only like discussing halal and haram laws and the prospect of discussion is only memorizing doctrinal propositions. On the other hand, PAI is then required to be friendly with social behavior and sensitive to the development of information and technology in this era 4.0. With descriptive qualitative research methods (library research) researchers try to examine and look deeper into Interdisciplinary Insightful Islamic Education for students as a feature and solution to the Era 4.0 Education. The results of this study obtained that the interdisciplinary approach that the researchers offer is to use the disciplines of Arabic, English, Information, and Technology (IT), Accounting and Ahlus Sunnah Wal Jama'ah (ASWAJA). With these 5 scientific disciplines, the Interdisciplinary PAI will be able to become the style and solution of the Islamic Education Era 4.0.